Incorporation of alpha-tocopherol into chitosan films: effects on film properties - Martins, Joana (2010)
Synthetic packaging films have led to serious ecological problems due to their non-biodegradability, being biopolymers an alternative source for packaging development. Polysaccharides have been exploited as a material for the development of edible films, and additionally can be used as carrier of functional compounds. The aim of this work was to evaluate the effects of the incorporation of -tocopherol in chitosan based films.